Women as Avengers: Semiotic Analysis of the Film Peppermint - Ramadhani, Aulia Rusyda; Hariyadi, Hariyadi; Santoso, Joko (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
In this study, the film used as the object of research is the film Peppermint which was released in 2018. This study aims to determine how the representation of masculinity in female characters and its relationship to acts of revenge due to legal injustice in the film Peppermint. Based on the results of the study, it can be seen that in the film Peppermint there is a form of masculinity played by the main female character, namely Riley. The forms of masculinity include the use of weapons and dark clothing, creating fear for their enemies, independent and rational nature, and courage. This indicates that women can adopt masculine roles as a strategy to face getting the rights and justice they seek. In addition, there is a link between masculinity depicted through the main female character, namely the character Riley using masculine behavior as a basis for carrying out acts of revenge.